Philosophical Review on the Meaning of the Term “Four Pillars” of MPR RI - Hastangka Hastangka; Armaidy Armawi; Kaelan Kaelan (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2019)
The use of the term “Four Pillars” by the People’s Consultative Assembly of the Republic of Indonesia (MPR RI) since the end of 2009 has generated numerous debates in Indonesian political life. The term of Four Pillars that consists of Pancasila, the 1945 Constitution, NKRI (Unitary State of the Republik of Indonesia), and Bhinneka Tunggal Ika (Unity in Diversity) is aﬀected by the essence, meaning, and understanding of the four in their original meanings. This research aims to examine and analysis on the philosophical problem of Four Pillars terms in the context of philosophy of language especially in the context of contestation of meaning and the essence of Four Pillars term in public discourse and debate. The research was conducted in 2014 to 2018 through literature studies in Yogyakarta. The research fnds that the term of “four pillars” since it was produced by political elites through the public education program has degraded and legitimized the meaning of Pancasila, the 1945 Constitution, NKRI (Unitary State of the Republic of Indonesia), and Bhinneka Tunggal Ika (Unity in Diversity). Philosophically, the use of term of four pillars for public education to introduce national insight conducted by the People’s Consultative Assembly of the Republic of Indonesia has distorting of meaning and displacing of meaning of Pancasila, the 1945 Constitution, NKRI, and Bhinneka Tunggal Ika. The term of “four pillars” is also not yet known in this history or by the public.